2012
DOI: 10.1242/dev.082024
|View full text |Cite
|
Sign up to set email alerts
|

Klf4 is required for germ-layer differentiation and body axis patterning duringXenopusembryogenesis

Abstract: SUMMARYKlf4 is a transcription factor of the family of Kruppel-like factors and plays important roles in stem cell biology; however, its function during embryogenesis is unknown. Here, we report the characterization of a Klf4 homologue in Xenopus laevis during embryogenesis. Klf4 is transcribed both maternally and zygotically and the transcript is ubiquitous in embryos during germ-layer formation. Klf4 promotes endoderm differentiation in both Nodal/Activin-dependent and -independent manners. Moreover, Klf4 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 45 publications
(42 reference statements)
1
30
0
1
Order By: Relevance
“…The embryos injected with Klf6 mRNA developed a slightly reduced head and significantly decreased posterior structure (Fig. 4E,L), a phenotype resembling Klf4 gain of function (Cao et al, 2012). Overexpression of Klf7 caused dramatic shortening of A-P axis, increased size of cement gland, reduced head structures, heavily pigmented belly protrusion in tail bud embryos, and incomplete closure of neural tube (Fig.…”
Section: Gain Of Function Analyses On Klf Factorsmentioning
confidence: 90%
See 4 more Smart Citations
“…The embryos injected with Klf6 mRNA developed a slightly reduced head and significantly decreased posterior structure (Fig. 4E,L), a phenotype resembling Klf4 gain of function (Cao et al, 2012). Overexpression of Klf7 caused dramatic shortening of A-P axis, increased size of cement gland, reduced head structures, heavily pigmented belly protrusion in tail bud embryos, and incomplete closure of neural tube (Fig.…”
Section: Gain Of Function Analyses On Klf Factorsmentioning
confidence: 90%
“…Previous studies have demonstrated that dorsal genes are regulated by different upstream signals, for example the Wnt and nodal pathways. Moreover, Klf factors are also involved in the regulation of Wnt, TGFb, or nodal signaling (Zhang et al, 2006;Boon et al, 2007;Truty et al, 2009;Cao et al, 2012;Sellak et al, 2012;Spittau and Krieglstein, 2012;Dionyssiou et al, 2013;Yi et al, 2014). It might be expected that Klf factors regulate gene expression in the dorsoventral patterning by means of regulation of Wnt or TGFb signaling.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations